Overview of Central Corneal Thickness in Patients with Glaucoma: A Single Center Observational Study at Dr. M. Djamil General Hospital, Padang, Indonesia - Prabowo, Harliady Dany; Andrini Ariesti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Central corneal thickness (CCT) is an important risk factor in the diagnosis and management of glaucoma. This study aims to determine the CCT picture of various types of glaucoma at Dr. M. Djamil General Hospital Padang. Methods: This descriptive retrospective study involved data from glaucoma patients at Dr. M. Djamil General Hospital Padang for the period January 2019 - December 2020. CCT data was obtained from medical records and OCT computer data. Descriptive analysis was carried out to see the distribution of CCT in ocular hypertension (OHT), glaucoma suspect (GS), normal tension glaucoma (NTG), primary open-angle glaucoma (POAG), and juvenile open-angle glaucoma (JOAG) groups. Results: A total of 123 glaucoma patients were analyzed. The overall mean CCT was 535.50 ± 43.82 µm. The highest mean CCT was in the OHT group (566.30 ± 32.07 µm) and the lowest in POAG (523.39 ± 39.43 µm). The mean age of patients was 35.19 ± 16.20 years. The POAG group had the highest mean age (52.52 ± 9.54 years), while the JOAG group had the lowest (22.00 ± 5.84 years). Conclusion: There are variations in CCT in various types of glaucoma, with OHT having the highest CCT and POAG the lowest. This data can be a basis for consideration in the diagnosis and management of glaucoma in Indonesia.